Negative affect increases reanalysis of conflicts between discourse context and world knowledge - Lai, Vicky Tzuyin; van Berkum, Jos; Hagoort, Peter (Frontiers in Communication, 2022)
Mood is a constant in our daily life and can permeate all levels of cognition. We examined whether and how mood influences the processing of discourse content that is relatively neutral and not loaded with emotion. During discourse processing, readers have to constantly strike a balance between what they know in long term memory and what the current discourse is about. Our general hypothesis is that mood states would affect this balance. We hypothesized that readers in a positive mood would rely more on default world knowledge, whereas readers in a negative mood would be more inclined to analyze the details in the current discourse. Participants were put in a positive and a negative mood via film clips, one week apart. In each session, after mood manipulation, they were presented with sentences in discourse materials. We created sentences such as “With the lights on you can see ...” that end with critical words (CW) “more” or “less”, where general knowledge supports “more”, not “less”. We then embedded each of these sentences in a wider discourse that does/does not support the CW (a story about driving in the night vs. stargazing). EEG was recorded throughout. The results showed that first, mood manipulation was successful in that there was a significant mood difference between sessions. Second, mood did not modulate the N400 effects. Participants in both moods detected outright semantic violations and allowed world knowledge to be overridden by discourse context. Third, mood modulated the LPC (Late Positive Component) effects, distributed in the frontal region. In negative moods, the LPC was sensitive to one-level violation. That is, CW that were supported by only world knowledge, only discourse, and neither, elicited larger frontal LPCs, in comparison to the condition where CW were supported by both world knowledge and discourse. These results suggest that mood does not influence all processes involved in discourse processing. Specifically, mood does not influence lexical-semantic retrieval (N400), but it does influence elaborative processes for sense making (P600) during discourse processing. These results advance our understanding of the impact and time course of mood on discourse.